The Effectiveness of Nutritional Therapy in Patient with Chronic Obstructive Lung Disease: A Systematic Review of Randomized Controlled Trials - Hasanudin Hasanudin; Taufan Arif; Nila Authoria; Ade Salma Yunia Rachmah; Achmad Tirmidzi (Universitas Airlangga, 2025)
Introduction: Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality worldwide and is often complicated by malnutrition and muscle wasting, which adversely affect prognosis. Although nutritional therapy has been recommended as part of comprehensive COPD care, the effectiveness of recent interventions has not been systematically evaluated. This systematic review aimed to evaluate the impact of nutritional therapy on clinical, functional, and patient-centered outcomes in individuals with COPD. Methods: Following the PRISMA guidelines, we searched Scopus, PubMed, EBSCO, and Nature for randomized controlled trials (RCTs) published between January 2020 and June 2025. Eligible studies included adult patients with COPD who received nutritional interventions. The risk of bias was assessed using the Cochrane RoB 2 tool. From 252 screened records, 13 RCTs involving 2,962 participants were included. Given the heterogeneity across interventions and outcomes, the findings were synthesized narratively. Results: The interventions included oral nutritional supplements, high-energy formulas, individualized dietary counseling, vitamin D, ω-3 fatty acids, and multi-nutrient combinations. Seven studies reported significant improvements in quality of life, six demonstrated gains in weight and nutritional status, and three showed increased muscle strength. Two trials observed enhanced physical activity, whereas both vitamin D studies found no overall protective effect against exacerbations, except in patients with severe deficiencies. The risk of bias was low in eight studies and raised concerns in five. Overall, the strength of evidence was moderate, limited by heterogeneity, and inconsistent outcome reporting. Conclusion: Nutritional therapy improves nutritional status and selected clinical outcomes in patients with COPD. Standardized, adequately powered RCTs are warranted to establish optimal protocols and to confirm long-term benefits.